THE GEBEL BARKAL STELAE AND THE DISCOVERY OF ANCIENT NUBIA: Auguste Mariette's Inspiration for Aïda - Schneider, Thomas 1964- (2015)
Giuseppe Verdi's opera Aïda, first performed in 1871, goes back to a scenario suggested in 1865 by French Egyptologist Auguste Mariette. It can be shown that Mariette took his inspiration from the five historical stelae discovered at Gebel Barkal on the fourth cataract of the Nile, the ancient Nubian capital city of Napata, in 1862, as well as some additional sources. Aïda is not an opera based on an actual historical narrative; however, it incorporates motifs attested in historical sources between the 8th and the 3rd centuries b.c.e. that were combined by Mariette in a historical collage. E.g., the priests' plot to kill an innocent man in the temple of Amun in Aspelta's Banishment Stela is paralleled by the trial and killing of the innocent Radames by priests in Aïda. This article situates the opera within the discovery of ancient Nubia in the later 19th century c.e.